What Does VECM Technique Reveal About India And Russia With Regard To Capital Inflows? - Sunny, Dolly; Unnikrishnan, Anupama (Advances in Social Sciences Research Journal, 2018)
Capital inflows enjoy extremely important role in the economic growth of developing countries. This makes the analysis of determinants of capital inflows in the developing countries extremely important. This paper tries to identify the determinants of capital inflows in India and Brazil using vector autoregression technique. First part gives an overview of Brazil and Indian economies. Second part describes earlier studies. Research methodology is explained in the third part and fourth part explains the data and variables used for the research. Fifth part deals with the results and the last part describes the conclusion.